Migration in Ireland Challenges, opportunities and policies - González Pandiella, Alberto (OECD Economics Department Working Papers, 2016)
The Irish labour market is exceptionally open to international migration flows, thus making labour supply highly responsive to changes in cyclical conditions. Immigration provides the skills that the Irish economy needs. The crisis triggered a sharp reversal in migration flows, with immigration suddenly halting and emigration increasing. A large proportion of emigration is highly qualified, as is a high proportion of immigration. This pattern of "brain exchange" can contribute to reducing skills mismatches, but also raises the challenge of remaining attractive for skilled workers. This paper examines how the crisis has affected migration, how related policies have evolved and proposes avenues to spread the benefits of migration beyond the scope of multinational enterprises, in particular to Irish SMEs. The proportion of Irish-born population living abroad is very large and the paper also analyses what role return migration could play, what policies are in place to maintain links with emigrant's communities abroad and how they can be strengthened. Ireland has recently experienced, for the first time in its history, large-scale immigration. As a result, it currently hosts a large and very heterogeneous immigrant community, with diverging challenges and needs. Getting integration policies right is therefore a complex, but crucial task. The paper identifies what are the key challenges in this area and proposes some avenues to foster the labour market integration of immigrants. Ireland is also starting to experience challenges associated with the integration of second generation immigrants. To respond to those challenges, the paper recommends early action in education and social domains